Tata Kelola Pendidikan Studi Kasus Tantangan Tata Kelola Pendidikan Islam di Daerah 3T: Analisis di Desa Parlampungan, Mandailing Natal - Pulungan, Hasmiah; Humairoh, Riski; Paizah, Nurul; Safitri, Rini (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study aims to analyze the challenges of Islamic education governance in Parlampungan village, Mandailing Natal 3T regions (Frontier, Outermost, and Disadvantaged), focusing on infrastructure, human resources, policy implementation, and the conflict between local values and national education approaches. A descriptive qualitative method was employed, utilizing literature reviews and case studies of Islamic educational institutions in 3T areas. The findings reveal systemic limitations, including inadequate facilities, shortage of qualified teachers, weak managerial capacity, and lack of contextualized policy support. Moreover, the tension between local cultural values and the standardized national curriculum poses a significant challenge, potentially undermining students' cultural identities. The study suggests the need for adaptive, community-based governance reforms, incorporating contextual curriculum development and capacity building for educators. These findings highlight the importance of an Islamic education governance model that is not only administratively accountable but also socially and culturally relevant to the unique realities of 3T regions.